Does cross-cultural communication training for physicians improve pediatric asthma outcomes? A randomized trial. (4th March 2019) - Patel, Minal R.; Song, Peter X. K.; Bruzzese, Jean-Marie; Hao, Wei; Evans, David; Thomas, Lara J.; Pinkett-Heller, Marcia; Meyerson, Karen; Brown, Randall W.
ABSTRACT: Objective : Adverse cross-cultural interactions are a persistent problem within medicine impacting minority patients' use of services and health outcomes. To test whether 1) enhancing the evidence-based Physician Asthma Care Education (PACE), a continuing medical education program, with cross cultural communication training (PACE Plus) would improve the asthma outcomes of African American and Latino/Hispanic children; and 2) whether PACE is effective in diverse groups of children. Methods : A three-arm randomized control trial was used to compare PACE Plus, PACE, and usual care. Participants were primary care physicians (n = 112) and their African American or Latino/Hispanic pediatric patients with persistent asthma (n = 867). The primary outcome of interest included changes in emergency department visits for asthma overtime, measured at baseline, and 9 and 21 months following the intervention. Other outcomes included hospitalizations, asthma symptom experience, caregiver asthma-related quality of life, and patient-provider communication measures. Results : Over the long term, PACE Plus physicians reported significant improvements in confidence and use of patient-centered communication and counseling techniques (p < 0.01) compared to PACE physicians. No other significant benefit in primary and secondary outcomes was observed in this trial. Conclusion : PACE Plus did not show significant benefit in asthma-specific clinical outcomes. More trials and multi-component strategies continue to be needed to address complex risk factors and reduce disparities in asthma care. Trial registration : ClinicalTrials.gov: NCT01251523 December 1, 2010. Trial registration: ClinicalTrials.gov identifier: NCT01251523.